Efektivitas Metode Bisik Berantai dalam Meningkatkan Keterampilan Menyimak di Kelas 6 SD 010140 - Rambe, Riris Nurkholidah; Rahmadani, Aulia; Utami, Putri; Masriana, Masriana; Ritonga, Yunizar; Marcela, Raya (TSAQOFAH, 2023)
The Purpose of this study wa to determine the effectiveness of the chain method in impoving listening skill ini 6 th SD 010140. the subject of this research is Mrs. Widiati a grade 6 teacher at SD 010140 Perk. Gunung Melayu Kecamatan Rahuning, Kabupaten Asahan, Provinsi Sumatera Utara. In this study researchers used qualitative methods, namely research and interpretation techniques that prodused descriptive data in the form of writing and word. The result of the research that has been done show that a chain of whispering games on listening skill in Bahasa Indonesia subjects in grade 6 greatly influences the learning process, which can make students happy and enthusiastic in learning. However this method also has disadvantages of students who are not conducive to making this method applied.